(untitled) (Canadian Medical Education Journal, 2022)
Background: The contributions of arts and humanities to medical education are known in the medical education community, but medical schools’ offerings vary. The Companion Curriculum (CC) is a student-curated set of optional humanities content for medical students at the University of Toronto. This study evaluates integration of the CC to identify key enabling conditions for medical humanities engagement. Methods: A mixed-methods evaluation gauged usage and perceptions of integration of the CC among medical students using an online survey and focus groups. Narrative data underwent thematic analysis, supported by summary statistics of quantitative data. Results: Half of survey respondents were aware of the CC (n = 67/130; 52%), and, once prompted with a description, 14% had discussed it in their tutorial groups. Of students using the CC, 80% reported learning something new regarding their roles as communicators and health advocates. Themes were the perceived value of the humanities, internal student barriers, institutional neglect of the humanities, and student critiques and recommendations. Conclusion: Despite participants’ interest in medical humanities, our CC remains underused. To improve humanities’ visibility in the MD curriculum, our results indicate that greater institutional support, including faculty development and early curricular integration, is required. Further study should explore reasons for gaps between interest and participation.